Transdermal Delivery of Anti-Obesity Compounds to Subcutaneous Adipose Tissue with Polymeric Microneedle Patches - Than, Aung (2017)
Excess white adipose tissue (WAT), or obesity, is the leading cause of many diseases. Combating obesity is, however, challenging due to the fact that laboratory-proven anti-obesity compounds lose effectiveness or/and cause severe side-effects while being delivered via conventional routes. Here, a new strategy is reported using disposable transdermal patches equipped with detachable polymeric microneedle (MN) arrays for painless and bloodless drug delivery to subcutaneous WAT. In contrast to the current methods to reduce energy intake, MN-patches are used to deliver anti-obesity compounds to increase energy expenditure by transforming calorie-storing white fat into calorie-burning brown fat. Specifically, prominent WAT browning and reduction effects are demonstrated by β3-adrenoceptor agonist and thyroid hormone T3 transdermally delivered from rapidly dissolving MNs on mice. Furthermore, using a diet-induced obese mouse model, it is shown that β3-adrenoceptor agonist released by slowly dissolving MNs can effectively promote WAT browning and suppress gaining of body fat and weight, without the need of daily administration. Such an MN approach can achieve a much lower effective dose as compared to systemic administration and enables long-term home-based treatment.